The spectrum of exudative pleural effusion: clinical and etiological insight - Bagal, Tamanna; Jamwal, Vinu; Gupta, Anil; Gupta, Abhinav (International Journal of Research in Medical Sciences, 2025)
Background: Pleural effusion, an abnormal accumulation of fluid in the pleural space, is classified as transudative or exudative using Light’s criteria. This study aimed to evaluate the clinical and etiological profile of exudative pleural effusion in a tertiary care center in a high-tuberculosis-prevalence region. Methods: This prospective study at Acharya Shri Chander college of medical sciences, Jammu (February 2024–January 2025), included 70 patients (14-85 years) with exudative pleural effusion. Demographics, clinical history, and investigations (X-ray, pleural/sputum analysis, CT) were recorded. Data were analyzed using excel and SPSS v20.0 with chi-square and Fisher’s exact tests. Results: The cohort was predominantly male (94.3%, p<0.001) with a mean age of 71.6±5.6 years. Common symptoms included cough (87.1%), dyspnea (77.1%), and fever (75.7%), with cough significantly associated with tuberculosis (p=0.02). Mean symptom duration was 2.7±1.2 weeks. Right-sided pleural effusion was most frequent (47.1%), followed by left-sided (27.1%) and bilateral (25.7%). Consolidation (22.9%) was significantly associated with pneumonia (p=0.01). Pleural fluid was exudative in 98.57% of cases, with malignant cells in 1.4%. Sputum analysis (n=53) showed AFB growth (35.84%) or CBNAAT positivity (50.94%), strongly associated with tuberculosis (p<0.001). Pulmonary tuberculosis was the leading etiology (74.3%), followed by pneumonia (8.6%), lung malignancy (1.4%), and undetermined causes (15.7%). Conclusions: Pulmonary tuberculosis is the leading cause of exudative pleural effusion in this cohort, with symptoms and imaging consistent with infection. The low malignancy rate, unlike Western data, highlights the need for region-specific diagnostics.